Applications of negative permeability metamaterials for electromagnetic resonance type wireless power transfer systems - Nie Kaiqi; Hou Qing (EPJ Applied Metamaterials, 2023)
With the development of electric drive systems such as unmanned aerial vehicles and electric vehicles, the charging problem of power supply devices has become increasingly prominent. However, the traditional charging method requires physical circuits, which makes it impossible to achieve freedom of the position in actual use. The wireless power transmission technology, which mainly relies on electromagnetic wave to complete energy transmission, is expected to get rid of the restriction of physical space location and solve the problem of charging location, which has great potential in medical treatment, rescue, detection and other fields. However, the low transmission efficiency and short transmission distance caused by electromagnetic field leakage are the two main problems faced by radio energy transmission systems. In general, with the increase of transmission distance, the transmission efficiency will drop sharply. Fortunately, inserting a negative permeability metamaterial with extraordinary electromagnetic characteristics into the transmitting and receiving coils will greatly alleviate this attenuation trend and can also shield electromagnetic radiation to a certain extent. In this paper, some experiments of negative permeability metamaterials used in electromagnetic resonance type wireless power transfer systems are summarized for reference.